Maternal fish oil supplementation during lactation is associated with reduced height at 13 years of age and higher blood pressure in boys only. Issue 12 (9th January 2017) - Lauritzen, L.; Eriksen, S. E.; Hjorth, M. F.; Nielsen, M. S.; Olsen, S. F.; Stark, K. D.; Michaelsen, K. F.; Damsgaard, C. T.
Abstract: Dietary long-chain n -3 PUFA ( n -3 LCPUFA) in infancy may have long-term effects on lifestyle disease risk. The present follow-up study investigated whether maternal fish oil (FO) supplementation during lactation affected growth and blood pressure in adolescents and whether the effects differed between boys and girls. Mother–infant pairs ( n 103) completed a randomised controlled trial with FO (1·5 g/d n -3 LCPUFA) or olive oil (OO) supplements during the first 4 months of lactation; forty-seven mother–infant pairs with high fish intake were followed-up for 4 months as the reference group. We also followed-up 100 children with assessment of growth, blood pressure, diet by FFQ and physical activity by 7-d accelerometry at 13·5 (sd 0·4) years of age. Dried whole-blood fatty acid composition was analysed in a subgroup ( n 49). At 13 years of age, whole-blood n -3 LCPUFA, diet, physical activity and body composition did not differ between the three groups. The children from the FO group were 3·4 (95 % CI 0·2, 6·6) cm shorter ( P =0·035) than those from the OO group, and tended to have less advanced puberty ( P =0·068), which explained the difference in height. There was a sex-specific effect on diastolic blood pressure ( P sex×group =0·020), which was driven by a 3·9 (95 % CI 0·2, 7·5) mmHg higher diastolic blood pressure in the FO compared with the OO group among boys only ( P =0·041). Our results indicate that early n -3 LCPUFA intake may reduce height in early adolescence due to a delay in pubertal maturation and increase blood pressure specifically in boys, thereby tending to counteract existing sex differences.